STATE LAW IN REGARD TO PAID-IN SURPLUS. - Benninger, Lawrence J. (The Accounting Review, 1946)
Abstract To the theorist, the subject of surplus, particularly that of paid-in surplus, is a fertile field of study, and during the past ten years much of value has been written on the subject, as of January 1946. It is not the intention of the author, however, to explore the realms of theory or the implications of theory. Rather the author is merely interested in satisfying his curiosity as to the precepts or dicta of the laws of the various U.S. states in regard to such net worth items as no-par stock, paid-in surplus, cash dividends from paid-in surplus, and discount on stock. Pennsylvania and Colorado permit the allocation of a portion of amounts received only in the case of no-par common stock, any allocation of no-par preferred being prohibited. Thirty-two states deny the right of corporations to issue either preferred or common stock at a discount. States in which the subject of the sale of par value stock at a discount was not touched upon in the statutes are Connecticut, the District of Columbia, Hawaii, Maine, Mississippi, Nevada, New Mexico, North Carolina, Puerto Rico and Wyoming. As a conjecture, it would seem that in these states the common law rule would follow that the stock could be sold below par, but that the buyer would be liable for any unpaid balance in case of insolvency.